Al-Riafah( Groundwater Extraction) By Arabs In Pre-Islamic Era Till The End Of Prophet Muhammad Peace Be Upon Him And The Caliphate - khrbotli, shokran; Enjamm, Raja (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Arabs lived in a desert environment, adopted where the springs explosive, although not exist they need to search for water and inferred and then deduced which is known to have the knowledge of Riyavh, which is a type of physiognomy as they need to search for some of the Numerology's to indicate the presence of water, usually what relied on sensing soil moisture, or sniff the smell, and smell the plants, and animal control to deduce the existence, and after discovering, they developed the tools and equipment for drilling and then Ensnarement to take advantage of this water Accumulated inside the earth, and they succeeded in that and have made great progress in making the necessary tools for lifting, and then slitting traction channels, as well as managed to build dams to trap rainfall, Riyavh was the science took a great importance in their lives.